2009
DOI: 10.14531/ss2009.3.20-29
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Extended Kyphotic Deformities of the Thoracic and Lumbar Spine

Abstract: To assess the efficacy of surgical treatment of kyphosis of various etiology, and to develop a differential etiology-based approach to the choice of surgical correction technique. Material and Methods. Seventy four patients with extended kyphotic deformities were operated on, including 13 patients with posttraumatic kyphosis; 13-with congenital kyphosis and kyphoscoliosis with a prevalence of kyphotic component; 7-with Scheuermann's kyphosis; 12-with dysplastic kyphoscoliosis; 11-with neurogenic kyphosis and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…Suk et al, reported a correction of 61.9 degress in the coronal plane and 45.3. degrees in sagittal plane in their seires of 70 patients. 9,10,11 In this case we corrected about 38 degrees in sagittal plane of deformity ( Figure 3). There was no complication after surgery, consider the patient was complete neurologic deficit from trauma.…”
Section: Discussionmentioning
confidence: 81%
“…Suk et al, reported a correction of 61.9 degress in the coronal plane and 45.3. degrees in sagittal plane in their seires of 70 patients. 9,10,11 In this case we corrected about 38 degrees in sagittal plane of deformity ( Figure 3). There was no complication after surgery, consider the patient was complete neurologic deficit from trauma.…”
Section: Discussionmentioning
confidence: 81%
“…Отказ от вентральной стабилизации ведет к несостоятельности ТПФ вследствие хронической перегрузки конструкций и усталостных переломов винтов, прорезыванию костных структур и их миграции. Это способствует рецидивам и нарастанию посттравматических деформаций позвоночного столба и, следовательно, позвоночного канала [1,2,4,5].…”
Section: Discussionunclassified
“…ТПФ рассматривается как временная стабилизация поврежденного ПДС, которую нужно дополнить межтеловым спондилодезом [1, 3-5, 10, 12, 14, 17]. В последние годы наибольшее распространение получили двухэтапные хирургические вмешательства [1,2,4,[8][9][10]16]. Первым этапом делают ламинэктомию и ТПФ, которая позволяет не только жестко стабилизировать поврежденный ПДС, но и производить реклинацию, репозицию и исправление оси позвоночника.…”
unclassified
“…Широкое использование дорсального инстру-ментария отодвинуло в тень вентраль-ные методики хирургического лечения [3,5,12]. Упоминание об использова-нии вентрального инструментария в отечественной литературе ограни-чивается единичными публикациями, освещающими пробный опыт лечения малого числа больных, страдающих сколиозом [1,2,4,6].…”
unclassified